2018
DOI: 10.1021/acs.jproteome.8b00081
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Chloroacetanilide Herbicides in Earthworm Coelomic Fluid Using1H NMR and GC–MS

Abstract: Earthworms ( Eisenia fetida) are vital members of the soil environment. Because of their sensitivity to many contaminants, monitoring earthworm metabolism may be a useful indicator of environmental stressors. Here, metabolic profiles of exposure to five chloroacetanilide herbicides and one enantiomer (acetochlor, alachlor, butachlor, racemic metolachlor, S-metolachlor, and propachlor) are observed in earthworm coelomic fluid using proton nuclear magnetic resonance spectroscopy (NMR) and gas chromatography-mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Various studies have shown that data combination from different detection techniques provides a comprehensive approach for metabolome coverage along with a better understanding of the underlying patho-physiological processes and the interplay of metabolic pathways, along with improved predictive accuracy, sensitivity and specificity of markers identified. [19][20][21][22][23] To the best of our knowledge, there are several metabolomic studies on radiation exposure using either LC-MS or NMR, but there are no reports stating the use of both of these techniques for data generation and integrated chemometric analysis for understanding of biological perturbations after radiation exposure. 5,[13][14][15][24][25][26] Therefore, combining the unique abilities of MS (high sensitivity) and NMR (reproducibility and ease of identification) followed by an integrated chemometric analysis has become a novel approach in the field of biomarker identification.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that data combination from different detection techniques provides a comprehensive approach for metabolome coverage along with a better understanding of the underlying patho-physiological processes and the interplay of metabolic pathways, along with improved predictive accuracy, sensitivity and specificity of markers identified. [19][20][21][22][23] To the best of our knowledge, there are several metabolomic studies on radiation exposure using either LC-MS or NMR, but there are no reports stating the use of both of these techniques for data generation and integrated chemometric analysis for understanding of biological perturbations after radiation exposure. 5,[13][14][15][24][25][26] Therefore, combining the unique abilities of MS (high sensitivity) and NMR (reproducibility and ease of identification) followed by an integrated chemometric analysis has become a novel approach in the field of biomarker identification.…”
Section: Introductionmentioning
confidence: 99%
“…For toxicological assessment, changes in metabolic profiles and their relationship to various biochemical pathways are investigated. Untargeted approaches have been used for this purpose, for instance, to explore the global impact of environmental chemical contaminants on earthworms (Griffith et al 2018 ) or on human cells (Hartung et al 2017 ), or to assess the impact of tobacco exposure on in vitro systems (Iskandar et al 2017 ; Kogel et al 2016 ; Zanetti et al 2017 ). For in vitro toxicology studies, two-dimensional (2D) cell cultures have been the most commonly investigated systems for decades.…”
Section: Introductionmentioning
confidence: 99%
“…It has benefited the emergence of new fields such as microbial metabolomics [19,20], and in particular the study the exometabolomes of bacteria without requiring chemical extractions or derivatizations of the samples [3,21,22,23,24,25]. This non-destructive and highly reproducible technique can detect a wide range of structural diverse compounds at micromolar concentrations [26]. NMR and mass spectrometry (MS) are widely used techniques for metabolomics and exo-metabolomics [27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%